Acessibilidade em viagens de avião: o cenário regulatório e as necessidades dos passageiros que demandam assistência especial - Souza, Jerusa Barbosa Guarda de (2014)
As an increase in air transport has been seen and studies have shown that passenger comfort is a competitive advantage for survival in the market, understanding the needs of users has proven to be crucial to the project. Knowing users also means knowing the passengers who require special assistance, an increasing group of air transport users. Currently, there are some regulations that seek to ensure the proper care for these passengers during flight and it has been seen a greater movement of regulatory authorities accordingly. Despite this normative movement, studies have shown that the care for these passengers is still deficient in airline industry. It occurs because the service provided can be accounted for the interaction between different social actors: aircraft manufacturers, regulators, air operators and users. Each of them has particularities and limitations that today are largely unexplored and fundamental for understanding the available service for these passengers. The objective of this research was to discuss the interaction of accessibility related aspects in air travel among different social actors. Attempting to achieve this goal, an exploratory research was conducted through qualitative approach. Procedures were semi-structured interviews in brazilian regulatory agencies; questionnaires assessing needs of the user group that fits into the studied category ; verification of air transport current conditions to assist this user group. Interviews with regulatory authorities as well as data of brazilian air transport current conditions were treated descriptively. Besides, the user survey was statisticaly done to characterize the population and it has employed the methodology of content analysis to identify the main problems concerning air transport, all arranged into categories and subcategories.The interview was done among 7 regulatory agencies, 419 passengers and the conditions of three Brazilian airlines were verified. The results of regulatory agencies interviews were compared to data from the literature, making use of concepts from institutional theory to highlight the structure and the role of those agencies in the development of accessibility laws. The results showed that almost all visited agencies perform functions concerning the development of laws as they also perform oversight functions or make people with disabilities aware. The results of passengers' interviews showed compatibility with data from the literature and also complemented the knowledge about it. The results and verification of current air transport conditions showed that most of recently inserted items in the resolution are not yet being followed by the airlines. According to all results, it was possible to synthesize and discuss a model of interaction of diverse social actors related to the accessibility aspects of air travel. It was concluded that the problems of air transport accessibility are mainly related to insufficient service provided by airport and aircraft operators, incomplete aircrafts facing real needs, inadequacy of standards for real needs of users. It has proved that a joint analysis among these actors can be effective ensuring air travel accessibility.